PENGEMBANGAN MATERI MOTIVASI BERORGANISASI BAGI SISWA KELAS X3 SMA NEGERI 2 TAMBANG KABUPATEN KAMPAR T.A 2013/2014 - Eko Budi Harsono; Sardi Yusuf; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract :One of the exertion that move in improving the quality of human resources is involved actively in the Organization. And for students can follow in the his school each. the environment is one of the determinants of the behaviour of a person be it a home environment, school, and community, the activities of the organization can help the formation of adolescent thought patterns. In Fact, not all students in a school are willing andinterested to the organizational activities, This is because many students assumed that the organization is an activity that is boring and not interesting. One way to deal with this is with the encourage mentor motivation of teachers,homeroom and guidance and counseling teacher in schools. The Refore, researchers found it necessary to develop amaterial about the motivation of the organization which is expected to be used by the teacher's guidanceand counselling to be given to their students. This material was compiled using the method ofresearch and development (R&D). The purpose of thisresearch is 1)Compile the material to the appropriate organizational motivation for students of class X 3 SMA Negeri 2 Tambang. 2) To find out the quality of the organizational motivation material produced. This material is validated by the supervising lecturer 1& 2, one of the lectures FKIP BK UR, a teacher mentor, 6 colleague, and 30 Students class X3 of Tambang senior high school 2 . This materials are gived to the students with the allocation 3 times (3 x 45 ').This material consistsof the meaning of motivation and organization, motivation theories, types of motivation and organization organizational characteristics,organizational elements and factors that affect the motivation of Association. Research results from the development of this material shows the quality of the material produced is in the category of "Good", with the acquisition of score for overall assessment of aspects of 3.37.Keywords: Development of guidance counseling materials, organizational motivation